A genome‐wide SNP genotyping resource for tropical pine tree species. (28th August 2021) - Jackson, Colin; Christie, Nanette; Reynolds, Sharon Melissa; Marais, Gerhard C.; Tii‐kuzu, Yokateme; Caballero, Madison; Kampman, Tamanique; Visser, Erik A.; Naidoo, Sanushka; Kain, Dominic; Whetten, Ross W.; Isik, Fikret; et al.
Abstract: We performed gene and genome targeted SNP discovery towards the development of a genome‐wide, multispecies genotyping array for tropical pines. Pooled RNA‐seq data from shoots of seedlings from five tropical pine species was used to identify transcript‐based SNPs resulting in 1.3 million candidate Affymetrix SNP probe sets. In addition, we used a custom 40 K probe set to perform capture‐seq in pooled DNA from 81 provenances representing the natural ranges of six tropical pine species in Mexico and Central America resulting in 563 K candidate SNP probe sets. Altogether, 300 K RNA‐seq (72%) and 120 K capture‐seq (28%) derived SNP probe sets were tiled on a 420 K screening array that was used to genotype 576 trees representing the 81 provenances and commercial breeding material. Based on the screening array results, 50 K SNPs were selected for commercial SNP array production including 20 K polymorphic SNPs for P. patula, P. tecunumanii, P. oocarpa and P. caribaea, 15 K for P. greggii and P. maximinoi, 13 K for P. elliottii and 8K for P. pseudostrobus . We included 9.7 K ancestry informative SNPs that will be valuable for species and hybrid discrimination. Of the 50 K SNP markers, 25% are polymorphic in only one species, while 75% are shared by two or more species. The Pitro50K SNP chip will be useful for population genomics and molecular breeding in this group of pine species that, together with their hybrids, represent the majority of fast‐growing tropical and subtropical pine plantations globally.